High and cold mining area water blocking layer reconstruction structure and method

By using water barrier structure constructed with improved soil and modified polyurethane in high-altitude mining areas, the problems of soil moisture leakage and frozen soil resource degradation in high-altitude mining areas are solved, and ecological restoration and resource utilization of coal gangue are achieved.

CN119466793APending Publication Date: 2025-02-18BEIJING FORESTRY UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411513119.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The backfill pits and external soil discharge sites in high-altitude mining areas have severe moisture leakage inside the soil and lack of heat insulation layers, which leads to the degradation of permafrost resources, affecting the restoration of vegetation and the sustainable development of ecological functions.

Method used

The water barrier layer reconstructs the structure of modified soil, modified polyurethane and modified soil. Through the combination of mixed materials of modified soil (gangue, loess, bentonite) and modified polyurethane, a dense water barrier layer is formed to prevent moisture from seeping. .

Benefits of technology

Effectively reconstruct the water barrier layer, reduce soil erosion, promote ecological restoration of mining areas, realize the resource utilization of coal gangue, and improve the materials' anti-freeze-thaw, compressive shear and anti-ultraviolet aging properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a high and cold mining area water blocking layer reconstruction structure and method. The water blocking layer reconstruction structure sequentially comprises improved soil, modified polyurethane and improved soil from bottom to top; wherein the improved soil is formed by mixing coal gangue, loess and bentonite in proportion; the modified polyurethane is obtained by dissolving an ultraviolet light absorber UV24 in a small amount of butanone, mixing with polyurethane, dissolving in water, and adjusting the pH value to 4-6. By reconstructing the water blocking layer, the effect of a previous frozen soil layer is achieved, water infiltration is effectively prevented, and water and soil loss of a mine is reduced. The ecological restoration of the mining area can be promoted, and the resource utilization of the coal gangue can be realized. The waterproof layer is reasonable in reconstruction structure, and the material is durable and practical. Through the structure of'improved soil + polyurethane + improved soil ', water infiltration is prevented to the greatest extent, and due to the added bentonite and ultraviolet light absorber, the freeze-thaw resistance, compression resistance, shear resistance and ultraviolet aging resistance of the material are enhanced, and the service life of the material is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the fields of mine ecological restoration and solid waste resource utilization, and in particular to a water-blocking layer reconstruction structure and method in a high-altitude and cold mining area. Background Art

[0002] The backfill pits and external dumping sites in high-cold mining areas are mainly composed of open-pit mining strippings (rocks and slag) and coal gangue. Most of the strippings and coal gangue have large particle sizes, which causes serious water leakage inside the soil. At the same time, the surface of the soil does not have an insulating layer composed mainly of non-capillary voids like the undisturbed natural profile. The strippings and coal gangue are often dark in color and easily absorb solar radiation and quickly conduct downward, causing the temperature inside the soil to be high. Therefore, the backfill pits and external dumping sites in high-cold mining areas have not been scientifically managed, and it is difficult or even impossible to form frozen soil in the low temperature season, that is, there is no seasonal frozen soil, which leads to a decrease in the water conservation capacity of the soil, thereby affecting vegetation recovery and even the sustainable development of ecological functions.

[0003] With global warming in recent years and the impact of human mining activities, the climate conditions in the Qilian Mountains have changed significantly. The lower limit of permafrost resources has gradually risen, and the permafrost temperature is degenerating. According to data, in the past decade, the upper limit of permafrost in the Juhugeng mining area has been 3.0~7.0m, and the upper limit of permafrost has decreased by 0~20cm / a. In order to restore permafrost in high-altitude mining areas, it is urgent to develop technologies to construct water-blocking layers at appropriate depths in the gangue profile to promote ecological restoration in mining areas. Summary of the invention

[0004] The purpose of the present invention is to provide a water-blocking layer reconstruction structure and method for high-altitude and cold mining areas.

[0005] In order to achieve the purpose of the present invention, in a first aspect, the present invention provides a water-blocking layer reconstruction structure in a high-cold mining area, which comprises, from bottom to top, improved soil, modified polyurethane and improved soil; The improved soil is prepared by mixing coal gangue, loess and bentonite in a mass ratio of 2:1:2; The modified polyurethane is obtained by dissolving the ultraviolet absorber UV24 in a small amount of butanone, mixing the mixture with polyurethane, dissolving the mixture in water, and adjusting the pH value to 4-6.

[0006] Furthermore, the particle size of the coal gangue is graded in a mass ratio of A:B:C=1:1:3.

[0007] Among them, A, B, and C are the particle size gradients of coal gangue, A: 5-2mm, B: 2-0.5mm, C: <0.5mm.

[0008] Furthermore, the particle size of the loess is 1-3 mm, preferably about 2 mm.

[0009] Furthermore, the bentonite has montmorillonite as a main component and has a white powder appearance.

[0010] Furthermore, the polyurethane may be W-OH. W-OH as a curing agent is a modified hydrophilic polyurethane composite material, which is a light yellow oily body with a density of about 1.18 g / cm 3 , can react with any proportion of water and solidify quickly in a few minutes.

[0011] Furthermore, the preparation method of the modified polyurethane is as follows: Dissolve the ultraviolet absorber UV24 in butanone, and then add it to the required mass fraction of W-OH to prepare a 3.5%-4.5% W-OH solution with a UV24 mass concentration of 0.06%-0.1%, and adjust the solution pH to 4-6; or

[0012] After dissolving the ultraviolet absorber UV24 in a small amount of butanone, add it directly to the W-OH solution with a concentration of 3.5%-4.5% to prepare a 3.5%-4.5% W-OH solution with a UV24 mass concentration of 0.06%-0.1%, and adjust the solution pH to 4-6.

[0013] Furthermore, the total thickness of the water-blocking layer reconstruction structure of the present invention is 8-10 cm, the thickness of the lower improved soil is 5-7 cm, and after compaction, 4-6 mm modified polyurethane is sprayed, and the thickness of the upper improved soil is 3-5 cm.

[0014] In a second aspect, the present invention provides the application of the structure in soil improvement and ecological restoration in high-altitude mining areas.

[0015] In a third aspect, the present invention provides a method for reconstructing a water-blocking layer in a high-cold mining area, comprising: (1) excavating a section, screening coal gangue, and removing large-volume stones; (2) recovering small-size coal gangue, mixing it with loess and bentonite in a mass ratio of 2:1:2, and then filling and compacting it to a thickness of 5-7 cm; (3) dissolving an ultraviolet absorber UV24 in a small amount of butanone, and then adding it to W-OH to prepare a UV24 mass concentration of 0.06%-0.1% and 3.5%-4.5% W-OH solution, and adjust the pH value of the solution to 4-6 to obtain modified polyurethane; or, after dissolving the ultraviolet absorber UV24 in a small amount of butanone, directly add it to the W-OH solution with a concentration of 3.5%-4.5% to prepare a 3.5%-4.5% W-OH solution with a UV24 mass concentration of 0.06%-0.1%, and adjust the pH value of the solution to 4-6 to obtain modified polyurethane; (4) spray the prepared modified polyurethane on the compacted improved soil layer at a spraying rate of 2.5~3.5L / m 2 , ensuring the thickness is 4-6mm; (5) After the modified polyurethane is cured, cover its surface with improved soil and compact it to a thickness of 3-5cm.

[0016] By means of the above technical solution, the present invention has at least the following advantages and beneficial effects: (1) The present invention achieves the effect of the previous frozen soil layer by reconstructing the water-blocking layer, effectively preventing water from infiltrating and reducing soil erosion in mines.

[0017] (ii) This method can use local materials and save costs. Using local coal gangue and loess as the main materials and adding a small amount of functional materials to reconstruct the water barrier layer can not only promote the ecological restoration of the mining area, but also realize the resource utilization of coal gangue.

[0018] (III) The water-blocking layer reconstruction structure provided by the present invention has a reasonable structure and durable and practical materials. The structure of "improved soil + polyurethane + improved soil" can prevent water infiltration to the greatest extent, and the added bentonite and ultraviolet absorber enhance the material's anti-freeze-thaw, compression and shear resistance, and anti-ultraviolet aging properties, greatly extending the material's service life. The polyurethane solution is adjusted to acidic to slow down its curing speed, making it more convenient to spray during specific construction. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a diagram showing the actual spraying effect of UV24 / W-OH in a preferred embodiment of the present invention.

[0020] Figure 2 This is a diagram of a soil column infiltration experimental device in a preferred embodiment of the present invention.

[0021] Figure 3 This is a diagram of a simulated rainfall experiment device in a preferred embodiment of the present invention. DETAILED DESCRIPTION

[0022] The present invention aims to provide a material and method for modifying and reconstructing a water-blocking layer in a high-cold mining area, which is used to enhance the water-blocking property of the water-blocking layer and accelerate ecological restoration in the mining area.

[0023] The present invention adopts the following technical solution: The matrix material for reconstructing the water-blocking layer in the mining area of ​​the present invention comprises improved soil and modified polyurethane (UV24 / W-OH). The reconstructed structure is improved soil, modified polyurethane and improved soil from bottom to top.

[0024] The improved soil is composed of coal gangue, loess and bentonite mixed evenly in a mass ratio of 2:1:2.

[0025] The gradation of the coal gangue is A:B:C=1:1:3; A, B, C are the particle size gradients of the coal gangue, A: 5-2mm, B: 2-0.5mm, C: <0.5mm. The particle size of the loess is 1-3mm. The bentonite is mainly composed of montmorillonite and has a white powder appearance.

[0026] Among them, the modified polyurethane is UV24 / W-OH prepolymer. A certain mass of ultraviolet absorber UV24 is dissolved in a small amount of butanone, and then W-OH added with the above UV24 is dissolved in tap water and adjusted (with sulfuric acid solution) to a UV24 / W-OH solution with a pH of 4-6.

[0027] The total thickness of the reconstructed water-blocking layer is 8-10 cm, the thickness of the lower improved soil is 5-7 cm, and after compaction, 4-6 mm of UV24 / W-OH solution with a concentration of 3.5-4.5% is sprayed, and the thickness of the upper improved soil is 3-5 cm.

[0028] The present invention provides a technical method for reconstructing a water-blocking layer in a high-cold mining area, comprising: (1) excavating a section, screening coal gangue, and removing large-volume stones; (2) recovering small-size coal gangue, mixing it with loess and bentonite in a mass ratio of 2:1:1, filling it in and compacting it to a thickness of 5-7 cm; (3) dissolving UV24 in butanone, and then adding it to W-OH to prepare a 3.5%-4.5% W-OH solution with a UV24 mass concentration of 0.06%-0.1%, and adjusting the solution to a pH of 4-6 to obtain a modified polyurethane; or, dissolving UV24 in a small amount of butanone, and directly adding it to a W-OH solution with a concentration of 3.5%-4.5%, to prepare a 3.5%-4.5% W-OH solution with a UV24 mass concentration of 0.06%-0.1%. W-OH solution, and adjust the solution to pH = 4-6 to obtain modified polyurethane; (4) spray the prepared modified polyurethane on the compacted improved soil layer at a spraying rate of 2.5-3.5 L / m 2 (5) After the modified polyurethane layer is cured, cover it with improved soil and compact it to a thickness of 3-5 cm.

[0029] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art, and the raw materials used are all commercially available products.

[0030] The ultraviolet absorber UV24 used in the following examples was purchased from Wuhan Shuer Biotechnology Co., Ltd.

[0031] Bentonite was purchased from Henan Borun Casting Materials Co., Ltd.

[0032] Polyurethane W-OH was purchased from Jiangsu A-Tech Environmental Engineering Design and Research Institute Co., Ltd.

[0033] Example 1 Method for reconstructing water-blocking layer in high-altitude and cold mining areas

[0034] The present invention provides a water-blocking layer reconstruction structure, which comprises, from bottom to top, improved soil, UV24 / W-OH (modified polyurethane), and improved soil.

[0035] The improved soil is made of coal gangue with a grading of A:B:C=1:1:3 (A, B, C are the particle size gradients of coal gangue, A: 5-2mm, B: 2-0.5mm, C: <0.5mm), loess with a particle size of 2mm, and bentonite, which are mixed in a mass ratio of 2:1:2.

[0036] The modified polyurethane is a UV24 / W-OH prepolymer, which is prepared into a 3.5%-4.5% UV24 / W-OH solution (i.e., modified polyurethane) with a pH of 4-6 and a UV24 mass concentration of 0.06%-0.1%.

[0037] UV24 / W-OH on-site spraying effect Figure 1 .

[0038] Example 2 Effect of W-OH concentration on permeability

[0039] The constant water head method was used to conduct soil column infiltration experiments. Figure 2 .

[0040] The retrieved gangue was kept in an oven at 105 °C for more than 4 h to ensure that the ore was dry and water-free, and passed through 5.0 mm, 2.0 mm, and 0.5 mm standard sieves to control the particle size to A: 2-5 mm, B: 0.5-2 mm, and C: < 0.5 mm. The gangue grading was set to A: B: C (1: 1: 3, mass ratio), and the gangue, loess, and bentonite were mixed evenly at a mass ratio of (2: 1: 2) to prepare the improved soil for later use. Gangue with a particle size of less than 5 mm was filled in the acrylic column in layers. After filling 20 cm, 7 cm of improved soil was continued to be filled. After compaction, 1.5%, 2.5%, 3.5%, 4%, and 4.5% UV24 / W-OH solution were sprayed respectively. The control group was not sprayed. After solidification, 3 cm of improved soil was filled and gangue was continued to be filled to make a soil column with a height of 50 cm and a diameter of 20 cm. The moisture sensor was arranged at a depth of 10, 20, 30, and 40 cm from the surface of the gangue. After 72 hours, the moisture sensors above the 3.5%, 4%, and 4.5% water-blocking layers all reached a stable value of about 66% VWC, that is, the moisture content of the gangue layer reached a saturated state, and no wetting front was seen below the water-blocking layer. The moisture sensor showed an initial value of 11.2% VWC, that is, there was no water infiltration. In the experimental group without spraying treatment, the wetting front reached the bottom of the soil column after 980 minutes. In the experimental groups with a concentration of 1.5% and 2.5%, the wetting front of the coal gangue below the water-blocking layer moved downward after 72 hours, and the moisture sensor values ​​below the water-blocking layer were 35% VWC and 20% VWC, respectively. The experimental results show that the polyurethane concentration has a great influence on the permeability of the water-blocking layer, and the preferred concentration is a polyurethane solution of 3.5%-4.5%. Overall, the permeability of the reconstructed water-blocking layer is poor, which prevents the infiltration of water.

[0041] Example 3 Effect of coal gangue particle size on permeability

[0042] The soil column infiltration experiment was conducted using the constant water head method. The retrieved gangue was kept in an oven at 105 °C for more than 4 h to ensure that the ore was dry and free of water, and passed through 5.0 mm, 2.0 mm, and 0.5 mm standard sieves to control the particle size to A: 2-5 mm, B: 0.5-2 mm, and C: < 0.5 mm. The sieved gangue was mixed evenly with loess and bentonite in a ratio of 2:1:2 to prepare improved soil for later use.

[0043] Among them, the gangue gradation is set to A:B:C mass ratios of (3:1:1), (1:3:1), (1:1:3). Gangue with a particle size of less than 5 mm is filled in layers in the acrylic column. After filling 20 cm, 10 cm of improved soil is continued to be filled. No polyurethane layer treatment is performed, and gangue is continued to be filled to make a soil column with a height of 50 cm and a diameter of 20 cm. The moisture sensor is arranged at a depth of 10, 20, 30, and 40 cm from the surface of the gangue. Among them, in the experimental group with a gradation of 3:1:1, the wetting front reaches the bottom of the soil column after 656 minutes, in the experimental group with a gradation of 1:3:1, the wetting front reaches the bottom of the soil column after 740 minutes, and in the experimental group with a gradation of 1:1:3, the wetting front reaches the bottom of the soil column after 980 minutes. The experimental results show that the grading of coal gangue has a great influence on the permeability of the water-blocking layer, and the small-particle fly ash has certain anti-freeze-thaw, compression and shear properties, so the preferred grading is 1:1:3.

[0044] Example 4 Effect of loess on permeability

[0045] The soil column infiltration experiment was conducted using the constant water head method. The retrieved gangue was kept in an oven at 105 °C for more than 4 h to ensure that the ore was dry and water-free, and passed through 5.0 mm, 2.0 mm, and 0.5 mm standard sieves to control the particle size to A: 2-5 mm, B: 0.5-2 mm, and C: < 0.5 mm. The gangue grading was set to a mass ratio of A: B: C (1: 1: 3). The gangue was mixed with loess in a mass ratio of (2: 1), (1: 1), and (1: 2), and a control group without loess was set up. The control group was not treated with a polyurethane layer, and a soil column with a height of 50 cm and a diameter of 20 cm was made. The moisture sensor was placed at a depth of 10, 20, 30, and 40 cm from the surface of the gangue. Among them, in the control group without loess mixing, the wetting front reached the bottom of the soil column after 290 minutes, and in the experimental groups with the gangue:loess mass ratio set to (1:2), (1:1), and (2:1), the wetting front reached the bottom of the soil column after 371 minutes, 411 minutes, and 501 minutes, respectively. The experimental results show that the gangue-soil ratio has an effect on the permeability of the mixed soil of gangue and loess, and the permeability is the weakest when the gangue-soil ratio is 2:1.

[0046] Example 5 Comparative test of material compression resistance

[0047] The retrieved gangue was kept in an oven at 105 °C for more than 4 h to ensure that the ore was dry and water-free, and passed through 5.0 mm, 2.0 mm, and 0.5 mm standard sieves to control the particle size of A: 2-5 mm, B: 0.5-2 mm, and C: < 0.5 mm. The gangue grading was set to A: B: C (1: 1: 3). The gangue, loess, and bentonite were mixed evenly in a mass ratio of 2: 1: 1 and 2: 1: 2, and a control group with a gangue ratio of 2: 1 without bentonite was set. After mixing evenly, it was poured into a 50 mm × 100 mm mold, and a standard specimen was prepared after absorbing water; finally, the prepared specimen was cured at room temperature for 72 h and then subjected to a uniaxial compression test. Among them, the compressive strength of the control group without bentonite is 20.62KPa, and the compressive strength of the experimental groups with mass ratios of 2:1:1 and 2:1:2 are 174.08KPa and 375.95KPa respectively. The experimental results show that the addition of bentonite greatly improves the overall compressive strength of the material. And bentonite itself also has a strong water holding capacity.

[0048] Example 6 Effect of UV24 on the UV resistance of materials

[0049] The 4% W-OH solution with UV24 added at mass concentrations of 0.02%, 0.04%, 0.06%, 0.08% and 0.1% was prepared, and the sieved coal gangue was placed in a culture dish with a diameter of 8 cm. The UV24 / W-OH solution was sprayed on its surface. After solidification and reaching a dry state, the sample was placed in a UV aging box for light irradiation experiment. Among them, the mass losses of the samples with UV24 added at concentrations of 0.02%, 0.04%, 0.06%, 0.08% and 0.1% were 1.5296g, 1.3267g, 1.0452g, 1.0437g and 1.0322g respectively. The experimental results show that the addition of UV24 can improve the anti-ultraviolet aging performance of W-OH solution, and the higher the UV24 concentration, the stronger the anti-ultraviolet performance, but when the UV24 concentration is higher than 0.06%, the anti-ultraviolet performance is not greatly improved.

[0050] Example 7 Effect of pH on Curing Time of W-OH

[0051] The pH value of W-OH solution was adjusted to 4, 6, 7, 8 and 10 with sulfuric acid and sodium hydroxide respectively, and its curing time was observed. The experimental results showed that with the increase of solution pH, the curing time became shorter, and the curing time was longest when the pH was acidic, i.e., pH=4-6.

[0052] Example 8 Simulated rainfall experiment

[0053] The retrieved gangue is air-dried and then sieved to remove large-volume gangue. First, fill the sieved gangue to a height of 10 cm, fill in 7 cm of improved soil after compaction, spray UV24 / W-OH solution after compaction, fill in 3 cm of improved soil after solidification, and continue to fill the gangue to a height of 30 cm after compaction. After the rainfall begins, use a high-precision stopwatch to record the initial runoff time, and record the 60-minute sediment volume, runoff volume and flow rate data after stable runoff. Ten minutes before the slope begins to produce runoff, the sediment runoff volume is sampled every 1 minute, and the flow rate is determined by the potassium permanganate tracer method. After 10 minutes of runoff, data is collected every 5 minutes. Sediment runoff volume treatment. The slope runoff volume is read out using a measuring cylinder. After the sediment volume is left to stand for 24 hours, it is poured into an aluminum box, dried in an oven at 105°C for 24 hours, and weighed and measured using a 0.01g precision balance. See the simulated rainfall experimental device for details. Figure 3 .

[0054] The experimental results show that the initial runoff time of the natural gangue slope is 302~660s, and the initial runoff time of the gangue slope with a water barrier is 136~563s. The initial runoff time with the water barrier is significantly reduced, and the larger the dose, the shorter the initial runoff time. The runoff process of the gangue slope is first rapid growth and then stable. The average runoff rate of the gangue slope with a water barrier is higher than that of the natural state, and the UV24 / W-OH application concentration is positively correlated with the average runoff rate. With the increase of UV24 / W-OH application and rainfall intensity, the slope flow velocity also increases. Under the same slope conditions, rainfall intensity has a significant impact on the average sediment yield rate of the slope; under different slope conditions, the average sediment yield rate is most significantly affected by rainfall intensity. Under the condition of 90 mm / h rainfall intensity, the average sediment yield rate increases by 45.43% compared with 60 mm / h; the average sediment yield rate of 15° and 25° slopes at 90 mm / h rainfall intensity is 1.854 g / (m 2 ·min)、2.00g / (m 2 ·min) is higher than 0.598g / (m 2 ·min)、0.709g / (m 2 ·min) increased by 210% and 182% respectively. In addition, within 1 hour of the rainfall experiment, no water infiltration occurred in the experimental group with a water-blocking layer.

[0055] In general, the reconstructed water-blocking layer is constructed of small-sized coal gangue, loess, bentonite and UV24 / W-OH, forming a dense and compact soil structure with a certain water absorption and water retention capacity, and poor water permeability, which can effectively prevent water from seeping from above. The bentonite and UV absorber UV24 contained in the structure can greatly improve the overall anti-freeze-thaw, compression and shear, and anti-aging properties of the structure, greatly extending its service life.

[0056] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. Reconstruction structure of water-blocking layer in high-cold mining area, characterized by: From bottom to top, they are improved soil, modified polyurethane, and improved soil; The improved soil is prepared by mixing coal gangue, loess and bentonite in a mass ratio of 2:1:2; The modified polyurethane is obtained by dissolving the ultraviolet absorber UV24 in a small amount of butanone, mixing the mixture with polyurethane, dissolving the mixture in water, and adjusting the pH value to 4-6.

2. The structure according to claim 1, characterized in that: The particle size of the coal gangue is graded in a mass ratio of A:B:C=1:1:3; Among them, A, B, and C are the particle size gradients of coal gangue, A: 5-2mm, B: 2-0.5mm, C: <0.5mm.

3. The structure according to claim 1, characterized in that: The particle size of the loess is 1-3 mm, preferably 2 mm.

4. The structure according to claim 1, characterized in that The bentonite has montmorillonite as a main component and is in the form of white powder.

5. The structure according to claim 1, characterized in that The polyurethane is W-OH.

6. The structure according to claim 5, characterized in that The preparation method of the modified polyurethane is as follows: Dissolve the ultraviolet absorber UV24 in butanone, and then add it to the required mass fraction of W-OH to prepare a 3.5%-4.5% W-OH solution with a UV24 mass concentration of 0.06%-0.1%, and adjust the solution pH to 4-6; or After dissolving the ultraviolet absorber UV24 in a small amount of butanone, add it directly to the W-OH solution with a concentration of 3.5%-4.5% to prepare a 3.5%-4.5% W-OH solution with a UV24 mass concentration of 0.06%-0.1%, and adjust the solution pH to 4-6.

7. The structure according to any one of claims 1 to 6, characterized in that: The total thickness of the water-blocking layer reconstruction structure is 8-10 cm, the thickness of the lower improved soil is 5-7 cm, and 4-6 mm modified polyurethane is sprayed after compaction, and the thickness of the upper improved soil is 3-5 cm.

8. Application of the structure according to any one of claims 1 to 7 in soil improvement and ecological restoration in high-altitude mining areas.

9. A method for reconstructing a water-blocking layer in a high-altitude mining area, characterized in that: include: (1) Excavate the section, screen the gangue, and remove the large stones; (2) Recover the small-size gangue, mix it with loess and bentonite in a mass ratio of 2:1:2, fill it in and compact it to a thickness of 5-7 cm; (3) Dissolve the ultraviolet absorber UV24 in a small amount of butanone, and then add it to W-OH to prepare a UV24 mass concentration of 0.06%-0.1% 3.5%-4.5% W-OH solution, and adjust the pH value of the solution to 4-6 to obtain modified polyurethane; or, after dissolving the ultraviolet absorber UV24 in a small amount of butanone, directly add it to the W-OH solution with a concentration of 3.5%-4.5% to prepare a 3.5%-4.5% W-OH solution with a UV24 mass concentration of 0.06%-0.1%, and adjust the pH value of the solution to 4-6 to obtain modified polyurethane; (4) spray the prepared modified polyurethane on the compacted improved soil layer at a spraying rate of 2.5~3.5L / m 2 , ensuring the thickness is 4-6mm; (5) After the modified polyurethane is cured, cover its surface with improved soil and compact it to a thickness of 3-5cm.